Origin of the neonatal gut microbiota and probiotic intervention: a randomized controlled trial - Li, Zhe; Zhang, Yiwen; Tan, Xiaozhi; Kian Deng, Tye; Gao, Qian; Xiao, Xiaomin; Xu, Chengfang (Frontiers in Nutrition, 2024)
Objective: This study aim to evaluate the origin of the neonatal gut microbiota in 14 th days and Probiotic intervention in the third trimester. Method: Samples were obtained from a total of 30 pregnant individuals and their offspring, divided into control group with no intervention and porbiotic group with live combined Bifidobacterium and Lactobacillus tablets, analyzing by 16S rRNA amplicon sequencing of the V4 region to evaluate the composition of them. Non-metric multidimensional scaling, SourceTracker were used to evaluate the origin of neonatal gut microbiota.We found that the microbiota in the neonatal gut in different time correlated with that in the maternal microbiota. Placenta had more influence on meconium microbiota. Maternal gut had more influence on neonatal gut microbiota in 3 rd day and 14 th day. We also found that the maternal gut, vaginal and placenta microbiota at full term in the probiotic group did not have a significantly different abundance of Bifidobacterium, Lactobacillus or Streptococcus. But some other bacteria changed in maternal gut and their neonatal gut in the probiotic group. Conclusion: Maternal gut microbiota was vital to their offspring. In our study, maternal gut, vaginal and placenta microbiota at full term in the probiotic group did not have a significantly different abundance of Bifidobacterium, Lactobacillus or Streptococcus. But maternal gut microbiota and their neonatal gut microbiota in the probiotic group might change after probiotic management in the third trimester.